CFD Analysis of Rear Spoiler Effects on Vehicles Aerodynamic Performance - Badu, Prajash; Panjiyar, Rahul; Guragain, Kushal; Yadav, Pankaj (OODBODHAN, 2024)
This study explores the aerodynamic properties of a sports car model, focusing on the impact of rear spoilers on vehicle's performance. Two car models are evaluated using the Computational Fluid Dynamics (CFD) simulation approach. The first basic model lacks a rear spoiler, whereas the second superior model features a rear NACA 2412 airfoil spoiler. The simulation was conducted at the indicated velocities: 100 km/hr., 180 km/hr., and 240 km/hr. to determine the impact of the spoiler, specifically drag force, lift force, and performance. The investigation shows that when a vehicle is traveling at a high speed, the rear spoiler increases stability and control by producing a significant amount of drag and down force. However, when the velocities are high, there is a rapid increase in drag force accompanied with an increase in lift coefficient, indicating that the spoiler has certain restrictions at high speeds. This can be a trade-off, as some researchers have discovered that a tiny increase in drag force results in an increase in down force. Overall, the advantages include stability and safety of the vehicle fleet. As a result, the study concludes that rear spoilers are critical in providing the appropriate level of downforce and reduced drag to the sports vehicle while also increasing overall road control, safety, and efficiency.